The Role of the Plant-Specific ALTERED XYLOGLUCAN9 Protein in Arabidopsis Cell Wall Polysaccharide O-Acetylation . Issue 4 (13th February 2015) - Schultink, Alex; Naylor, Dan; Dama, Murali; Pauly, Markus
Abstract : The Arabidopsis AXY9 gene encodes a plant-specific component of a cell wall polysaccharide acetylation pathway. Abstract: A mutation in the ALTERED XYLOGLUCAN9 ( AXY9 ) gene was found to be causative for the decreased xyloglucan acetylation phenotype of the axy9.1 mutant, which was identified in a forward genetic screen for Arabidopsis ( Arabidopsis thaliana ) mutants. The axy9.1 mutant also exhibits decreased O -acetylation of xylan, implying that the AXY9 protein has a broad role in polysaccharide acetylation. An axy9 insertional mutant exhibits severe growth defects and collapsed xylem, demonstrating the importance of wall polysaccharide O -acetylation for normal plant growth and development. Localization and topological experiments indicate that the active site of the AXY9 protein resides within the Golgi lumen. The AXY9 protein appears to be a component of the plant cell wall polysaccharide acetylation pathway, which also includes the REDUCED WALL ACETYLATION and TRICHOME BIREFRINGENCE-LIKE proteins. The AXY9 protein is distinct from the TRICHOME BIREFRINGENCE-LIKE proteins, reported to be polysaccharide acetyltransferases, but does share homology with them and other acetyltransferases, suggesting that the AXY9 protein may act to produce an acetylated intermediate that is part of the O -acetylation pathway.